Kebijakan Kepala Sekolah dalam Mengembangkan Kurikulum Islam Terpadu Di SMP IT Al Bayan - Fatwa, Marhatul; Mesiono (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to describe the principal's understanding of the Integrated Islamic curriculum, the form of policies applied in curriculum development, and teachers' perceptions of these policies at Al-Bayan IT Junior High School. This research uses a qualitative approach with a case study method. Data were obtained through in-depth interviews with the principal, vice principal for curriculum, and teachers. The results showed that the principal has a comprehensive understanding of the Integrated Islamic curriculum as a curriculum that integrates academic aspects and Islamic values. The policies taken by the principal are strategic and collaborative, including the integration of Islamic values in lesson plans, tahfidz programme, adab habituation, and teacher training. Teachers responded positively to the policy, although further coaching is still needed. This research confirms the importance of the principal's role as a leader, innovator and evaluator in supporting the implementation of an integrated Islamic curriculum effectively and sustainably.